Investigating the effectiveness of idiom intervention for 9–16‐year‐olds with developmental language disorder. Issue 2 (22nd December 2019) - Benjamin, Lucy; Newton, Caroline; Ebbels, Susan
Abstract: Background: Idiom skills are essential for children to access age‐appropriate media, curriculum resources and teaching. Children with developmental language disorder (DLD) require support to develop the ability to understand and define idioms. However, research investigating one‐to‐one and classroom‐based idiom skill intervention for children with DLD is limited. Aims: To investigate the effectiveness of one‐to‐one speech and language therapist (SLT) and classroom‐based interventions to develop and maintain progress of the idiom skills of 9–16‐year‐olds with DLD. Methods & Procedures: Forty‐nine 9–16‐year‐olds from a specialist school for children with DLD received 20 intervention sessions to develop idiom skills during two school terms. Following a baseline period, 24 participants (aged 11–16) received ten 30‐min one‐to‐one SLT intervention sessions once per week for the first term and classroom‐based intervention for the second term. A total of 25 participants (aged 9–16) received the same intervention in the reverse order. Classroom‐based intervention was delivered collaboratively by English teachers and SLTs during English lessons. All participants were assessed on their ability to identify, interpret, explain and use idioms 3 months before, directly before and after each intervention and 3 months post‐intervention, using a bespoke assessment including 48 idioms randomly assigned to three sets: one‐to‐one intervention, classroom‐based intervention and control idioms. Outcomes & Results: Participants made significantly more progress during the intervention blocks than during the baseline period (block 1: d = 1.91; block 2: d = 1.01) and post‐intervention levels were maintained 3 months post‐intervention. Idiom skills showed significant progress when targeted through both one‐to‐one ( d = 2.18) and classroom‐based intervention ( d = 0.91) but one‐to‐one intervention was significantly more effective than classroom‐based intervention ( d = 0.63). Examination of the specific idiom skills targeted revealed that although idiom identification and interpretation skills did not progress significantly more during intervention blocks than the baseline period, idiom explanation (block 1: d = 1.02; block 2: d = 0.97); and use did (block 1: d = 0.94; block 2: d = 0.81). One‐to‐one intervention was more effective than classroom‐based intervention for developing idiom explanation ( d = 1.32) and use ( d = 0.65). Progress on control items was not significantly different during intervention blocks than during the baseline period overall or for any of the individual idiom skills. Conclusions & Implications: Both one‐to‐one SLT and classroom‐based intervention are effective (although one‐to‐one is more effective) for teaching and maintaining idiom skills, particularly explanation and use. This means that SLTs and English teachers can help children to develop idiom skills which may enable better access to the curriculum and popular media.